Análise crítica na interpretação dos parâmetros de avaliação do agente físico ruído - Maia, Sérgio Emygdio Cabral (2009)
This study presents a critical analysis of the interpretation of the evaluation parameters of the physical agent Noise, from a comparative analysis of the technical criteria used in the noise exposure evaluations. More specifically, it focuses on the divergences between the Norma de Higiene Ocupacional (Occupational Hygiene Norm) 01 (NHO 01) from Fundacentro, which deals with the evaluation of the exposure to noise, and those criteria established by the Norma Regulamentadora (Regulation Norm) 15 (NR15) of the Ministério do Trabalho e Emprego (MTE) (Work Department). The interest on this subject came when I was working in the implementation of the Safety Consulting and Occupational Health, specifically when quantitative assessments of physical agent noise by audio dosimetry were done, I noticed that methodologies and procedures differed in a legal manner. The most recent update of the Normative Instructions, to Nº 27, April 30, 2008, in Article IV of Article 180 paragraph states that: From 19 November 2003, the framework will be made when the NEN is over eighty-five dB (A) is exceeded or the unit dose, applying: a) the tolerance limits set out in Table I of Annex 15 of the NRMTE; b) the methods and procedures defined in the NHO Fundacentro-01. Hence the conflict. This requires a broad and urgent review and standardization of methodologies for the best from the point of view of workers, for the effective protection of workers exposed to Agent Physical Noise. For example, the NR-15 doubles the factor of 5 is higher than the NHO-01 that is 3, by determining a prevention less accurate, but the reverse appears on the Criterion of Action Level. The proposed analysis points mainly to the following conclusions: as Fundacentro is an official organ, the NHO 01 parameters should be used as a complement to those established in the Annex 1 of the NR 15, as to avoid criteria or methodology conflicts; noise evaluation through dosimeters seems to be the most adequate, precise and reliable mode of obtaining a noise report